ASCORBIC ACID SUPPLEMENTATION FOR ADJUNCTIVE TREATMENT OF PULMONARY TUBERCULOSIS: REVIEW OF LABORATORY RESEARCH AND CLINICAL TRIALS IN INDONESIA - Rakasiwi, Muhammad Ilham Dhiya; Taufik, Muhammad; Aristyo, Kevin; Wandawa, Azlina D; Burhan, Erlina; Kurniawan, Gerry; Ferian, Muhammad Farel (Universitas Tadulako, 2024)
Background: Tuberculosis (TB) is a highly lethal global disease caused by Mycobacterium tuberculosis (Mtb), which has affected approximately a quarter of the world's population. Ascorbic acid is acknowledged for its strong antioxidant properties, its ability to modulate the immune system, and its effectiveness against Mtb infections. Method: Literature search based on specific keywords following the PICO (Patient, Intervention, Comparison, Outcome) research question was carried out on Pubmed, Scopus and Google Scholar databases, as well as Garuda for clinical research in Indonesia. The flow of the literature search followed PRISMA and risk of bias analysis using the Rob2 tool. Discussion: Laboratory studies have shown that ascorbic acid, whether given by itself or in conjunction with standard anti-TB medications, can decrease the quantity of Mtb colony-forming units (CFU). Similar outcomes were witnessed in experiments conducted with mice. The administration of ascorbic acid to mice infected with Mtb also led to a reduction in lung tissue damage. Clinical trials carried out in Indonesia demonstrated that the addition of ascorbic acid resulted in a greater sputum conversion rate in comparison to patients who did not receive this supplementation. Conclusion: Ascorbic acid exhibits several clinical attributes that prove beneficial in the management of TB.